EXPLORING GENDER BIAS AND DISCRIMINATION EXPERIENCES AMONG FEMALE HOCKEY PLAYERS - Sharma, Seema Kaushik; Jaggi, Virender Singh; Sharma, Rekha; Pillai, Madhvi Pathak (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study aimed to explore the gender bias and experiences of discrimination among female hockey players. A self-made questionnaire was administered to 18 participants aged between 11 and 27, collecting data on social support and self-perception. The questionnaire included Likert-scale items, and the responses were transformed into percentile statistics for analysis. The findings revealed significant experiences of gender discrimination by referees during tournaments and coaches during practice/competitions. Bullying by senior athletes and incidents of sexual harassment were also reported, highlighting the presence of such issues within sports environments. The participants’ awareness of these incidents and their perception of existing laws addressing sexual harassment varied. However, most participants believed in sports’ empowering role financially for women and the importance of gender parity in competition prizes and boarding/lodging facilities. Support for establishing a committee to address gender bias in sports was moderately expressed. These results emphasize the need to address and rectify gender biases, discrimination, and harassment in women’s hockey and promote inclusive and equitable sporting environments.